Prevalence of Listeria spp. in Seafood Samples and Control of Listeria monocytogenes with Using LISTEX™ P100 Bacteriophage Applications in Smoked Rainbow Trout - Hatice Gündüz; Fatma Öztürk (Journal of Agricultural Sciences)
This study was carried out to determine the presence of Listeria spp. in seafood and determine the effect of LISTEX™ P100 bacteriophage applications (incorporated into the sodium alginate based film and applied directly to the surface) on the smoked trout. In this study, Listeria spp. was isolated in 40 of the 100 products analyzed. Among the Listeria isolates, 8% correspond to L. monocytogenes, 15% to L. innocua, 6% to L. seeligeri, 10% to L. welshimeri, and 15 to L. grayi. L. ivanovii was not detected in any of the products analyzed. LISTEX™ P100 bacteriophage as antimicrobial compounds was incorporated into the sodium alginate based film for the first time. Bacteriophage in sodium alginate based film and direct bacteriophage applications in smoked trout were found to be effective in L. monocytogenes inactivation during storage. In addition, the preservation of phage stability of the two groups during storage indicates that in the smoked products can use in the control of L. monocytogenes.